Evaluation of the TDWI BI and AI Maturity Model on SMEs and Non-Profit Organizations at State Vocational High School 7, Tangerang Regency - Isman Hidayat; Alfa Ryano Yohannis (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
The TDWI Maturity Model for Business Intelligence (BI) and Artificial Intelligence (AI) has been widely adopted as a framework for assessing the level of BI and AI adoption in various organizations. However, its application has so far focused on large enterprises, leaving little exploration of its relevance and suitability for small and medium enterprises (SMEs) and non-profit organizations, particularly in Indonesia. This study aims to evaluate the relevance of the TDWI BI and AI Maturity Model questionnaire in the context of vocational high schools (SMK) and non-profit educational institutions, identify contextual gaps, and propose adaptations to improve its implementation and effectiveness. A qualitative research approach with thematic analysis was used to analyze data from four key respondents: a principal, a curriculum coordinator, an IT operator, and a teacher. The analysis focused on the alignment of the TDWI model with the organizational, technical, and social contexts of the schools. The research findings indicate that, although the TDWI model is conceptually relevant, several adaptations are needed to make it more applicable in educational settings. Suggested adaptations include simplifying technical language to make it understandable for non-technical staff, integrating data literacy and resource-based indicators to assess staff readiness and organizational capacity, and adding a social impact dimension to evaluate the contribution of BI and AI to educational quality and equitable access to learning. Six critical themes emerged as challenges to implementing the TDWI model in schools: language clarity, financial context, organizational structure, resource constraints, digital literacy, and social impact. Addressing these themes could improve the localization of the global maturity model, making it more relevant to SMEs and non-profit educational institutions. This study expands theoretical and practical understanding of the application of BI and AI frameworks beyond large corporations, emphasizes contextual adaptations, and provides guidance for school administrators, policymakers, and educational technology practitioners.